The Role of the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) in Addressing Violence Against Women and Children in Denpasar City - Anak Agung Ayu Krisna Dewi; Ni Luh Made Mahendrawati; Ni Komang Arini Styawati (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
In accordance with the Regulation of the Minister of Women’s Empowerment and Child Protection Number 4 of 2018 concerning Guidelines for the Establishment of Regional Technical Implementation Units for the Protection of Women and Children, subsequently operationalized at the local level through the Regulation of the Mayor of Denpasar Number 25 of 2018, the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) is entrusted with the statutory duty to provide protection services and to administer the handling and resolution of cases involving violence against women and children. Nevertheless, despite the institutional establishment of the UPTD PPA, the number of violence cases remains relatively high, and many incidents are still unreported, resulting in victims not receiving proper protection and follow-up handling. This condition diverges from the principal objective underlying the establishment of the UPTD PPA, which is intended to prevent, mitigate, and address acts of discrimination and violence against women and children. Accordingly, this study adopts an empirical legal research method employing a juridical, empirical approach to examine legal provisions in conjunction with their implementation in societal practice. The study findings indicate that the implementation of the UPTD PPA’s role has not yet operated effectively, primarily due to the complexity of violence cases that require coordination among various institutions with different authorities and functional responsibilities, thereby affecting the optimal delivery of protection and case-handling services.